Dissociação clinicorradiológica em lactente com tuberculose pulmonar: relato de caso - Débora Elisabeth Sales Vieira; Rafael José Souza Filho; Rebecca da Silva Sales Vieira; Ana Carolina Gonçalves Galeano Arco; Juliènne Martins Araújo; Clarissa Netto dos Reys Laia Franco Prillwitz; Christiane Mello Schmidt; Claudete Araújo Cardoso (Residência Pediátrica)
Pulmonary tuberculosis (TB) is a preventable treatable and infectious disease caused by Mycobacterium tuberculosis (Mtb). The infection occurs through the inhalation of droplets expelled by an individual with the active disease. Most cases develop latent infection, and a minority manifest the active form of the disease. As in adults, TB in children has predominantly pulmonary involvement, and usually present with non specific symptoms such as fever, respiratory distress, cough, weight loss or no gain, rales and wheezing. The etiological diagnosis is difficult due to the reduced number of bacilli in the lesions. This is the case of a 5 month old infant, female, previously healthy, with a persistent cough for three months, with chest wheeze and inappetence, but without manifestation of fever. The chest X-ray showed extensive lung consolidation affecting the entire right hemithorax. During hospitalization, the patient showed no improvement in the radiological appearance despite the use of broad-spectrum antibiotics. The diagnosis of Mtb infection was confirmed by a polymerase chain reaction test (Xpert Ultra MTB-RIF®). The patient was discharged to complete the treatment - rifampicin-isoniazid-pyrazinamide in an outpatient clinic with good clinical outcome. Due to the particularities of pediatric TB, highlightining the non-specificity of the signs and symptoms and the paucibacillary lesions, one must beawared of this diagnosis, especially in the presence of radiological clinical dissociation.